The bacterial composition signatures of perianal abscess and origin of infecting microbes - Song Han; Wenya Su; Kefeng Fan; Zhen Xu; Hai Xu; Mingyu Wang; Ling Li; Wenlong Shen (PeerJ)
Background Perianal abscess is a common anal condition primarily caused by bacterial infections, yet the precise origins of these infecting bacteria remain unclear. Understanding the distinct microbial signatures associated with periaabscesses is crucial for provide fresh ideas for disease prevention. Materials and Methods Samples of anal skin, feces, and abscesses were collected from a cohort of 75 patients diagnosed with perianal abscesses. The microbial composition at each site was analyzed using 16S rRNA gene sequencing to characterize the bacterial communities present. Results Analysis using MaAslin2 revealed distinct bacterial compositional signatures among the anal skin, feces, and abscess samples. Alpha diversity analysis indicated significant differences in bacterial diversity between abscesses, anal skin, and feces, with abscesses showing lower diversity compared to higher richness in feces. Biomarker analysis highlighted key taxa such as Bacteroides and Escherichia-Shisgella in fecal samples, and Staphylococcus and Corynebacterium in anal skin samples. The analysis of abscess samples suggested that the bacterial composition may originate from the skin, feces, and potentially other sources.